Globalisasi, Warisan Budaya, dan Pariwisata: : Implikasi Terhadap Hubungan Antar Bangsa - Jumariah Bela Kusuma; Khairunisa Fahrina; Titik Nur Fadilla (Public Knowledge, 2025)
This research explains the influence of globalization on cultural heritage in the Riau Islands, namely Teater Bangsawan, as one of the tourism attractions in the Riau Islands. Globalization provides challenges through changing societal preferences and declining interest in traditional Malay culture, but also opens opportunities through the utilization of social media for international promotion of local artists. By combining aspects of globalization, cultural heritage preservation, and the impact of tourism, this research offers in-depth insights into how relations between nations can be shaped and strengthened through efforts to preserve and develop local cultural heritage, particularly in the context of noble theatre in the Riau Islands. This research examines the complex interactions between globalization, cultural heritage, and tourism, and their impact on relations between nations. In an era of intensified globalization, cultural heritage is becoming an important asset in the global tourism industry. However, it also poses challenges in maintaining the authenticity and sustainability of cultural heritage. This study aims to analyze how globalization affects the representation and interpretation of cultural heritage in the context of tourism, as well as its implications for cultural diplomacy and relations between nations. This research uses a descriptive qualitative approach, with data obtained through literature studies obtained from various sources. The results show that globalization and tourism can be a catalyst for the revitalization of cultural heritage, but also have the potential to cause value conflicts and cultural commodification. The study concludes that a balance is needed between tourism development and cultural heritage preservation to ensure harmonious and sustainable relations between nations.